Application of specialised in situ tests in Changi East reclamation projects, Singapore. Issue 1 (29th November 2018) - Bo, Myint Win; Lwin, Tun; Choa, Victor
Abstract : A land reclamation and ground improvement project requires an extensive study of underlying soils, fill material, performance of ground improvement works and shore-protection structures. The area of the Changi East project in Singapore is underlain by soft compressible soils, which will be filled with a greater thickness of granular soil; the project will create shore-protection structures. Therefore, the large magnitude of settlement and stability of shore-protection structures were major issues for the project. A ground improvement and engineering design process was required. This process required a detailed and comprehensive study of the ground profile and characterisation of underlying soils and fill material. Characterisation and interpretation of geotechnical parameters of soils applying specialised in situ testing has become popular due to its unique feature of measuring parameters under in situ conditions. The measured data from specialised in situ tests can be interpreted to obtain geotechnical parameters quickly in addition to soil classification and profiling without the need to collect samples. This paper presents application of specialised in situ tests as well as interpretation of measured data for land reclamation and ground improvement projects. This paper also discusses how these in situ testing methods were utilised to monitor and verify the progress of ground improvement.